Exploring Student Learning Concentration Through Whatsapp Group: A Classroom Teacher's Effort in Online Learning During The Pandemic - Juhji Juhji; Ahmad Riduan; Syaepudin Syaepudin; Dira Afrina Liani (CV FOUNDAE, 2022)
This study analyzes the teacher's efforts in increasing student concentration in online learning and the role of parents in assisting their children's learning. The method used in this research is a survey method. The data collection technique used was interviews with teachers and parents of students at MIN 2 Serang and MIN 4 Serang. The data from the interviews were analyzed and then concluded in the form of a narrative. The study results reveal that teachers can know the concentration of their students when they learn to use video call media. In addition, parents play a role in assisting their children's learning. These findings indicate that teachers have increased students' learning concentration. It is proven effective in increasing students' learning concentration, marked by an increase in learning outcomes, and students' parents provide learning assistance to their children. The study recommends that teachers use video calls to overcome the concentration of students' learning and learning assistance for students at home by their parents.